INFLUENCE OF SOCIAL FACTORS ON THE ADOPTION OF THE ROLL BACK MALARIA PROGRAMME AND MATERNAL HEALTH IN IBADAN, NIGERIA (2015)
Malaria contributes substantially to maternal mortality in Nigeria, especially in Ibadan, which is a holo-endemic area. Despite the introduction of the Roll Back Malaria (RBM) programme, evidence shows that the incidences of maternal mortality due to malaria persist. Most studies on malaria have focused on preventive behaviour related to environmental and hygiene practices; however little attention has paid to how social factors influence adequate treatment procedure, case management and use of insecticide treated nets (ITNs), which are components of the RBM initiative, particularly during pregnancy. This study, therefore, examined the influence of social factors such as education, marital status and income on the adoption of the RBM programme. Social Action theory and Health Belief Model were employed as frameworks. The study adopted a cross sectional survey design using multistage sampling technique. Six health centres (one in each local government areas where the RBM programme is prominent) were purposively selected. A semi-structured questionnaire on background characteristics, knowledge, acceptability and adherence to RBM programme were administered to 407 pregnant women based on attendance records in the health centres. Knowledge of malaria, Acceptability of RBM and Adherence to RBM scales were used for data collection. In-depth interviews were also conducted with 13 RBM staff and 24 pregnant women based on records of malaria incidence. Quantitative data were analysed using descriptive statistics, Chi-square and Logistic regression tests at p ≤ 0.05, while qualitative data were content analysed. The age of respondents was 27.9±5.1 years, 79.0% had post-primary education, mean monthly income was N8,519:34K, 74.0% were self-employed and 59.2% were primigravidae. Although the respondents did not identify RBM as a distinct programme, their knowledge of malaria (χ2 = 21.58) significantly influenced their adoption of RBM programme; decision making (χ2 = 23.03); and use of ITNs (χ2 = 10.95). There was a significant relationship between knowledge of RBM programme and maternal health (β = 0.22). A unit increase in the knowledge of RBM caused 0.8 unit improvement in maternal health. There was a strong relationship between the acceptability of RBM program and maternal health (β = 0.15); a unit increase in the acceptability of the RBM strategy led to 0.86 unit improvement in maternal health. Respondents’ marital status (χ2 = 16.82), monthly income (χ2 = 7.04) and parity (χ2 = 16.39) significantly influenced their adherence to RBM programme, while religion, education, and occupation were not significant. Late registration for Antenatal Clinic made strict adherence to RBM programme difficult; inadequate supply of ITNs, drugs and manpower were major limitations to the effective implementation of the programme. Social factors largely influenced the adoption of the Roll Back Malaria programme among pregnant women in Ibadan. Increased awareness of the programme and empowerment of women of childbearing age, as well as availability of sufficient tools and services in order to significantly reduce the incidence of malaria are of utmost importance.